2012
DOI: 10.1080/1573062x.2012.660960
|View full text |Cite
|
Sign up to set email alerts
|

Cost-benefit analysis – leakage reduction by rehabilitating old water pipelines: Case study of Oslo (Norway)

Abstract: Water saving is not just the responsibility of the consumer. While demand-side management prescribes several good practices for water-consumers, the supplier also understands that leakage reduction on its part is a more effective mode of saving large quantities of water, by having to abstract, treat and supply less. It is not just water which is saved, but money spent on chemicals and energy expended on treatment and pumping. The economic aspect apart, this also means that there are possibilities of significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 15 publications
(30 reference statements)
2
13
0
1
Order By: Relevance
“…This finding supports the conclusion of Venkatesh (2012); that even in a system with high leakage rates, repairing broken pipes is more effective than a high replacement rate. The results in Gothenburg were also in line with Sánchez et al (2005) and van der Kleij and Stephenson (2002), who found that having more personnel using traditional methods for leakage detection was more beneficial than installing permanent acoustic loggers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding supports the conclusion of Venkatesh (2012); that even in a system with high leakage rates, repairing broken pipes is more effective than a high replacement rate. The results in Gothenburg were also in line with Sánchez et al (2005) and van der Kleij and Stephenson (2002), who found that having more personnel using traditional methods for leakage detection was more beneficial than installing permanent acoustic loggers.…”
Section: Discussionsupporting
confidence: 90%
“…when the number of burst pipes exceeded 2 per km per year, considering only direct costs. In Oslo, Venkatesh (2012) performed a CBA case study where the cost of pipe replacement was much higher than the benefits associated with the reduction in leakage; however, this CBA covered only a short period of time; 10 years, and although extending the time period ought to narrow the gap, this would not be enough to justify pipe replacement for the purpose of leakage reduction alone. None of the case studies mentioned took into account health effects due to pipe failure repairs, nor were environmental effects included as costs.…”
Section: Introductionmentioning
confidence: 97%
“…A low willingness to pay for improvement in environmental performance is clearly a conflict between the environmental goals and the socio-economic ones. However, a controlled reduction of excessive operating pressures in water systems results in a reduction of the volume of leakage and the frequency of burst pipes (Johnson 2012, Venkatesh 2012. If pressure management is adopted as a strategy to reduce water leakages, the need to hike the water/sewage fees would not arise.…”
Section: Awareness Of Conflicts/synergies With Non-environmental Goalsmentioning
confidence: 98%
“…Short-term infrastructure costs to municipalities thus need to be balanced with long-term public good benefits from decreased water withdrawals. Similarly, reductions in imported water, cost savings from lowering pumping costs, reductions in carbon intensity of water systems, and other benefits often accrue to the water provider in response to conservation, but may be hard to measure and credit (Venkatesh, 2012). Aligning incentives properly at different scales is an ongoing challenge for technocratic, deliberative, participatory, collaborative, and market-based methods.…”
Section: Finance Pricing and Innovationmentioning
confidence: 99%